Validation of the attitude scale to lesbian, gay,bisexual and transgender old age in a Colombian sample (2022)
The Attitude Scale to Lesbian, Gay, Bisexual and Transgender Old Age (EAFV-LGBT) evaluates attitudes towards LGBT older adults. The main goal of this research was to adapt and examine the psychometric properties in a Spanish-speaking sample. The sample consisted of 521 Colombian adults (36.3% men and 63.7% women) with a mean age equal to 27.39 (SD = 9.27). Participants completed a Socio-Demographic and Sexual History Questionnaire, the Hispanic translations of the EAFV-LGBT, the Subtle and Manifest Prejudice Scale towards Homosexuals, and the Big Five Personality Trait Short Questionnaire. The results showed that the Colombian EAFV-LGBT has good psychometric properties. The structure of the scale was unidimensional, and the internal consistency reliability was also adequate. Likewise, the convergent validity of the scale was verified by correlating it with another measure that evaluates explicit and implicit homophobia. In addition, it was found that there was a relationship between personality traits and attitudes towards LGBT adults. Specifically, participants with lower openness, extraversion, and agreeableness reported more negative attitudes toward older LGBT people.